A Longitudinal Study of Incarceration and HIV Risk Among Methadone Maintained Men and Their Primary Female Partners - Epperson, Matthew W. (2011)
This study examines the longitudinal relationship between personal and sexual partner incarceration and subsequent HIV risk behaviors among drug-involved men and their primary female sexual partners. A random sample of 356 men in methadone treatment in New York City were interviewed at baseline, 6 and 12 months; these men also reported information on their primary female sexual partners. Female partner recent incarceration was associated with subsequent increase in multiple partnerships for the male participants (AOR: 3.31; 95% C.I.: 1.26–8.72, P < .05). Female partner incarceration was also associated with reduced likelihood of subsequent unprotected sex between primary partners (AOR: .13; 95% C.I.: .05–.40, P < .01); this finding is somewhat unique and warrants further investigation. Findings support the notion of mutual influence in the case of female partner incarceration, which is associated with both female partner and male partner risk behaviors. HIV prevention implications are discussed, including the need for couple-based HIV prevention interventions targeting couples affected by incarceration.